Kinetic, thermodynamic, and isosteric heat of dibutyl and diethyl phthalate removal onto activated carbon from Albizzia julibrissin pods. (17th February 2018) - Bouhamidi, Y.; Kaouah, F.; Nouri, L.; Boumaza, S.; Trari, M.; Bendjama, Z.
ABSTRACT: The adsorption performance of diethyl and dibutyl phthalates on a new activated carbon prepared from an abundant biomass " Albizzia julibrissin Pods, " treated chemically by H3 PO4 is investigated through the equilibrium and kinetic study. The effect of different parameters like contact time, initial phthalate concentrations, and temperature on the adsorption capacities was studied in batch mode to evaluate the optimal conditions. Adsorption isotherms for both phthalates were fit at different temperatures using the Langmuir and Freundlich nonlinear regression. Adsorption kinetics were adjusted to various linear models, such as pseudo-first-order, pseudo-second-order, liquid film diffusion, intraparticle diffusion, and Boyd. The thermodynamic analysis indicated that the adsorption was spontaneous and exothermic in nature. The adsorption isosteric heat revealed a heterogeneous surface with different adsorption sites activities.